Individual entrepreneurial orientation, entrepreneurship education and entrepreneurial intention: The mediating role of entrepreneurial motivations. Issue 4 (August 2021) - Hassan, Aamir; Anwar, Imran; Saleem, Imran; Islam, K.M. Baharul; Hussain, Syed Abid
This paper examines the direct and indirect roles of individual entrepreneurial orientation and entrepreneurship education in determining students' entrepreneurial intention through the mediation of entrepreneurial motivations. The study also attempts to ascertain the influence of entrepreneurship education on individual entrepreneurial orientation. Cross-sectional data were collected from 323 university students using the convenience sampling method. Confirmatory factor analysis was used to assess the model fitness and the reliability and validity of the data while hypotheses were tested using structural equation modeling. The findings affirm that entrepreneurship education facilitates both individual entrepreneurial orientation and entrepreneurial motivations and also has a positive association with entrepreneurial intention. More importantly, entrepreneurial motivations significantly mediate individual 'entrepreneurial orientation–entrepreneurial intention' and 'entrepreneurship education–entrepreneurial intention' relationships. The findings provide practical support for the framing of new educational policies to assist students in their existing and future entrepreneurial projects. The study contributes to the literature by recognizing the mediating effect of entrepreneurial motivations on the above relationships. It also adds to the scarce literature on the lately recognized individual entrepreneurial orientation construct.